Effects of a low intensity resistance training program in overweight/obese and pre menopausal/menopausal women - Rodrigo Ramirez Campillo; Cristian Álvarez Lepín (Universidade Federal de Santa Catarina, 2013)
Obesity-related complications may be compounded by the detrimental consequences of menopause. Strength training programs may have an impact on this relationship. Our objective was to examine strength (1RM) and kinanthropometric alterations for overweight/obese pre- and menopausal women who participated in a strength program. Methods: 35 women were separated into: overweight premenopausal (n=8),obese premenopausal (n=9), overweight menopausal (n=8) and obese menopausal (n=10)categories. Participants attended a strength program for 8 weeks. Kinanthropometric characteristics and 1RM were determined at baseline, week 4 (except 1RM) and week 8. Results: All groups reduced (p< 0.05) body weight, body mass index (BMI), skinfolds and waist circumference. Furthermore, all groups achieved an increase (p< 0.05) in 1RM. When grouped per menopausal state or BMI, a more significant increase in strength was seen in menopausal and obese subjects. A significant correlation was observed for menopausal state, BMI and strength. The strength changes were significantly superior vs. kinanthropometric changes. Within kinanthropometric changes, skinfolds exhibit amore significant reduction vs. body weight, BMI and waist circumference. Conclusions: all groups showed changes in strength and kinanthropometric parameters. Strength adaptations were superior in menopausal and obese women. The strength adaptations exhibit a superior magnitude vs. kinanthropometric changes. In short term, a strength program may lead.